A Corpus-Based Comparison of the Chief Executive Officer Statements in Annual Reports and Corporate Social Responsibility Reports - Liu, Qingrong; Bilal,; Komal, Bushra (Frontiers in Psychology, 2022)
This study presents a corpus-based comparison of CEO statements between annual reports and corporate social responsibility reports. Using a corpus of 209 CEO statements from annual reports and CSR reports issued by Chinese companies, this study employs semantic domains generated by a corpus-tool Wmatrix to investigate the main concerns of CEOs in these two related reports. The results showed that corporate leaders tend to have different priorities in annual reports and CSR reports. In annual reports, corporate leaders highlight pragmatic aspects to create a professionally capable and objective corporate image. In CSR reports, corporate leaders highlight ethical aspects to create a socially responsible corporate image and adopt a more engaging and affiliative voice. This study has significance in understanding the differences in the related genres of annual reports and CSR reports.